Comparison of Invasive Left Atrial Pressure Between Bachmann's Bundle and Right Atrial Appendage Pacing. - Tan, Eugene S. J.; Lim, Wei Yao; Kailasam, Anand; Lee, Jie Ying; Tan, Li Wei; Leong, Kevin; Yeo, Wee Tiong; Seow, Swee‐Chong (Pacing & Clinical Electrophysiology, 2026)
Introduction: Bachmann's bundle pacing (BBP) is associated with shorter p‐wave duration (PWD) and reduced atrial fibrillation (AF) recurrence compared to right atrial appendage pacing (RAAP). We investigated the differences in acute left atrial pressure (LAP) measured invasively between sinus rhythm, BBP and RAAP. Methods and Results: Acute LAP and PWD were measured in subjects undergoing left atrial catheter ablation in sinus rhythm, during BBP and RAAP at the end of ablation. Differences in PWD and LAP were determined by paired t‐tests. Among 26 subjects (age 56.6 ± 14.2years, 27% female, 11% left‐sided accessory pathway ablation, 54% pulmonary vein isolation[PVI], 35% PVI+additional LA ablation), BBP was successful in 24 subjects. Adjusted for age, only PWD was significantly associated with LAP in sinus rhythm (ß 0.12, p = 0.039). Compared to sinus rhythm and RAAP, BBP was associated with significantly shorter PWD (p < 0.05), but LAP was not significantly different (p > 0.05). In subgroup analyses, BBP remained associated with significantly shorter PWD, but was also associated with lower acute LAP compared to RAAP (16.7 ± 5.5 mmHg vs. 17.0 ± 6.0 mmHg, p = 0.010), among patients with interatrial conduction delay, defined as PWD>120 ms during sinus rhythm. Acute LAP was similar between BBP, sinus rhythm and RAAP in other subgroups (paroxysmal vs. persistent AF, PVI vs. PVI+additional LA ablation, left ventricular ejection fraction <50% vs. ≥50%; all p > 0.05). Conclusion: Reductions in PWD during BBP did not correspond with uniform reductions with acute LAP. Acute LAP was lower in BBP than RAAP, but its clinical significance in reducing AF requires further study.